ANALYSIS OF THE RESPONSIBILITY OF REGIONAL DISASTER MANAGEMENT AGENCIES IN HANDLING POST-DISASTERS OF FLOODS IN ACEH SINGKIL - Sinta Hartina; Delfi Suganda; Zakki Fuad Khalil (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Indonesia is a country with a high level of vulnerability to natural disasters due to its geographical location and tropical climate. Aceh Province is among the regions prone to disasters, particularly floods that strike various districts almost every year. Aceh Singkil District is one of the areas with high risk, influenced by geographical factors, coastal conditions, and high rainfall. The high poverty rate and the prevalence of underdeveloped villages further increase community vulnerability to the impacts of flooding, especially during the post-disaster phase. In such conditions, the role of the Regional Disaster Management Agency (BPBD) becomes crucial in providing rapid, accurate, and sustainable responses to restore community conditions. This study aims to analyze the responsiveness of BPBD Aceh Singkil in handling post-flood disasters, identify existing challenges, and offer recommendations for improving the quality of public services in the disaster management sector. The research employs a descriptive qualitative method with data collected through in-depth interviews, observations, and documentation. Research informants consist of BPBD officials and flood-affected community members. The analysis refers to the public service quality theory by Zeithaml, Parasuraman, and Berry, using five responsiveness indicators: service speed, proactive attitude, accuracy of targeting, transparency, and ease of access. Theoretically, this study is expected to enrich public administration discourse related to government institutional responsiveness. Practically, it provides evaluation and recommendations for BPBD Aceh Singkil to enhance the effectiveness of post-flood disaster management. Therefore, this study is expected to contribute to improving disaster governance that is more responsive and adaptive for communities in disaster prone areas.